2021
DOI: 10.1002/ijgo.13546
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of titrated oral misoprostol solution versus vaginal dinoprostone for induction of labor: A single‐center randomized control trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In addition, vaginal dinoprostone insert (Propess) appeared to function safely, with a low incidence of complications. The rate of oxytocin augmentation was low at 25%, similar to the rates reported in some previous studies ( 13 ,14). Only 4 women (3.92%) experienced uterine tachysystole.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, vaginal dinoprostone insert (Propess) appeared to function safely, with a low incidence of complications. The rate of oxytocin augmentation was low at 25%, similar to the rates reported in some previous studies ( 13 ,14). Only 4 women (3.92%) experienced uterine tachysystole.…”
Section: Discussionsupporting
confidence: 89%
“…Only 4 women (3.92%) experienced uterine tachysystole. Other studies have reported that vaginal dinoprostone produced uterine hyperstimulation in approximately 10% of pregnant women but with no serious adverse maternal or fetal outcomes ( 13 ,15). This once again confirms that prostaglandin E2 is effective at stimulating uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis of direct randomised comparisons 11 suggests low‐dose oral misoprostol reduces the need for birth by caesarean and rate of hyperstimulation, but is otherwise of similar efficacy and safety to the standard dinoprostone regimens, and there may be potential logistical advantages of the oral regimen (oral administration, low cost, and heat stability). The largest study to date 12 randomly allocated 4395 women to titrated oral misoprostol solution 20–50 micrograms 1–2 hourly or vaginal insert dinoprostone 10 mg. Those given oral misoprostol had a significantly lower caesarean birth rate (21.7% vs. 27.0%) and significantly less hyperstimulation (3.6% vs. 8.6%).…”
Section: Misoprostolmentioning
confidence: 99%
“…In KBTH, the protocol for induction of labour using misoprostol has evolved over the past decades with specific revisions aimed at improving both the perinatal and maternal outcomes. 19 The use of OMS has been found to be equally effective compared with vaginal route in systematic review by Hofmyer et al 20 Similarly, OMS was found to be associated with lower induction to delivery interval and less side effect compared to vaginal misoprostol in a recent RCT in Egypt. In Ghana, the use of OMS is not well integrated.…”
Section: Resultsmentioning
confidence: 97%
“…In a recent randomized trial in China, titrated OMS for IOL resulted in a lower CS rate (21.7% versus 27%) and tachysystole with fetal heart rate abnormalities (3.6% versus 8.6%) compared to vaginal dinoprostone. 19 The use of OMS has been found to be equally effective compared with vaginal route in systematic review by Hofmyer et al 20 Similarly, OMS was found to be associated with lower induction to delivery interval and less side effect compared to vaginal misoprostol in a recent RCT in Egypt. In Ghana, the use of OMS is not well integrated.…”
Section: Discussionmentioning
confidence: 97%